DINAMIKA POPULASI IKAN KEMBUNG LELAKI (Rastrelliger kanagurta) DI TELUK KUPANG, PROVINSI NUSA TENGGARA TIMUR, INDONESIA - Restituta Kurnia; Yahyah yahyah; Lumban Nauli Lumban Toruan (Jurnal Perikanan dan Kelautan, 2023)
Indian mackerel (Rastrelliger kanagurta) in the waters of Kupang Bay is part of the wealth of biological resources that the population needs to be maintained in order to be sustainable. The rate of exploitation Indian mackerel fish is due to the large market demand and high levels of consumption, causing many fishermen to carry out continuous fishing. This research aims to analyze Indian mackerel fishstock as a basis for policies for fisheries management in the waters of Kupang Bay. The research was conducted in September 2022. Total sample of fish was 150. The data collected includes length and total weight. Data analyzed used Microsoft Excel and FISAT II software. The results of the analysis of the long-weight relationship between male and female mackerel showed that the growth pattern was negatif allometric with estimated of growth parameters L∞ = 28.40 cm, K = 0.51 years, and t0 = -0.32 years. The total mortality rate (Z) was 4,68, the natural mortality rate (M) was 1,17, the mortality rate from fishing (F) was 3,5, and the exploitation rate (E) was 0,75 per year.